VIABILITY OF WEED SEED BANK UNDER DIFFERENT EFFECTS OF WEED CONTROL IN LENTIL - A. M. Sultan (Mesopotamia Journal of Agriculture)
Weed seeds bank experiment was carried out to determine the viable numbers of weed after different weed control methods in lentil in Talkief and Namrood locations in Naniva provancy during winter season 2008-2009. Soil samples had been taken after lentil harvesting. Three factors used in this experiment tillage system (Zero tillage (Z.T.) + Gramaxon (Gr) , Zero tillage (Z.T.) + Glyphosate (Gl) , Zero tillage (Z.T.) , Conventional tillage (C.T.). Different seeding rate (S.R.) of lentil used (100, 120, 140 kg/ha). Also different irrigation systems (rainfall and supplementary irrigation (S.I.) of lentil had been used. Date were subjected in R.C.B.D. as split- split plots with four replications. The result indicated that weed seed population was significantly reduced under rainfall when compared to (S.I.) in Talkief and Namrood location which gave 14.9% , 88.5% for grasses weed seed (G.W.S.) and 13.2% , 64.4% for broad leaves weed seeds (B.W.S.) in two locations respectively. Under (C.T.) system had a significant lower number of (G.W.S.), in two locations while the lower numbers of (B.W.S.) had seen at (Z.T. + Gr.) in this two locations. On other hand , lowest (G.W.S.) was in 120 kg/ha of (S.R.) in two locations while (B.W.S.) was different in that two locations, which lower number had recorded in (140 and 100 kg/ha) in talkief and Namrood, respectively. The highest number of (G.W.S.) were recorded at (Z.T. + Gl.) under (S.I.) with 140 kg/ha (S.R.) in Talkief and under the same condition but with (Z.T.) at Namrood location.